Comparison of acute physiological responses between one long and two short sessions of moderate-intensity training in endurance athletes - Kjøsen Talsnes, Rune; Torvik, Per-Øyvind; Skovereng, Knut; Sandbakk, Øyvind (Frontiers in physiology, 2024)
To compare acute physiological responses and perceived training stress between one long and two short time- and intensity-matched sessions of moderate-intensity training in endurance athletes. Fourteen male endurance athletes (VO : 69.2 ± 4.2 mL·min ·kg ) performed one 6 × 10-min interval session (SINGLE) and two 3 × 10-min interval sessions interspersed with 6.5 h recovery (DOUBLE) of moderate-intensity training on two separate days, while running in the laboratory, using a counterbalanced cross-over trial. The two training days were separated into a first part/session (interval stage 1-3) and second part/session (interval stage 4-6). Respiratory variables, heart rate (HR), blood lactate concentrations (BLa), and rating of perceived exertion (RPE) were collected during sessions, whereas supine heart rate (HR) was assessed in a 60-min recovery period following sessions. Measures of perceived training stress (1-10) were assessed in the morning of the subsequent day. HR, Bla, and RPE increased in the second compared to first part of SINGLE (168 ± 7 vs. 173 ± 7 bpm, 2.60 ± 0.75 vs. 3.01 ± 0.81 mmol·L , and 13.4 ± 1.0 vs. 14.8 ± 1.1-point, respectively, all < 0.05). HR and Bla decreased in the second compared to first session of DOUBLE (171 ± 9 vs. 166 ± 9 bpm and 2.72 ± 0.96 vs. 2.14 ± 0.65 mmol·L , respectively, both < 0.05). SINGLE revealed higher supine HR in the recovery period following sessions (65.4 ± 2.5 vs. 60.7 ± 2.5 bpm < 0.05), session RPE (sRPE, 7.0 ± 1.0 vs. 6.0 ± 1.3-point, = .001) and sRPE training load (929 ± 112 vs. 743 ± 98, < 0.001) compared to DOUBLE. In the subsequent morning, increased levels of perceived fatigue and muscle soreness were observed following SINGLE compared to DOUBLE (7.0 ± 2.5 vs. 8.0 ± 1.0-point, = .049 and 6.0 ± 2.5 vs. 7.0 ± 2.5-point, = .002, respectively). One long moderate-intensity training session was associated with a duration-dependent "drift" in physiological responses compared to two short time- and intensity-matched sessions, thereby suggesting a higher overall training stimulus. Simultaneously, the lower cost of the two shorter sessions indicates that such organization could allow more accumulated time at this intensity. Overall, these findings serve as a starting point to better understand the pros and cons of organizing moderate-intensity training as one long versus shorter sessions performed more frequently (e.g., as "double threshold training") in endurance athletes.